2013
DOI: 10.1007/s12035-013-8401-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of Resveratrol Against Aβ Administration in Rats are Improved by Lipid-Core Nanocapsules

Abstract: Alzheimer's disease (AD), a neurodegenerative disorder exhibiting a gradual decline in cognitive function, is characterized by the presence of neuritic plaques composed of neurofibrillary tangles and amyloid-β (Aβ) peptide. Available drugs for AD therapy have small effect sizes and do not alter disease progression. Several studies have been shown that resveratrol is associated with anti-amyloidogenic properties, but therapeutic application of its beneficial effects is limited. Here we compared the neuroprotect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
82
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(87 citation statements)
references
References 74 publications
3
82
0
2
Order By: Relevance
“…The mechanisms of encapsulation and release of several drugs from nanoparticle-based systems have been extensively studied by our group. 25,[35][36][37][38] Here, the high α-bis loading capacity of LNCs was a consequence of its concomitant use as a core constituent and active ingredient, leading to an apparent solubility in water of ~10 mg mL −1 in the α-bis-LNCs.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of encapsulation and release of several drugs from nanoparticle-based systems have been extensively studied by our group. 25,[35][36][37][38] Here, the high α-bis loading capacity of LNCs was a consequence of its concomitant use as a core constituent and active ingredient, leading to an apparent solubility in water of ~10 mg mL −1 in the α-bis-LNCs.…”
Section: Discussionmentioning
confidence: 99%
“…34,152,162 Resveratrol has multiple health benefits, including antiaging, anticancer, cardioprotective, and PD protective effects. 66,68,145 Resveratrol exists in cis and trans forms, in which trans-resveratrol is more stable than cis-resveratrol which is pharmacologically less active.…”
Section: Nanoresveratrolmentioning
confidence: 99%
“…9,11,60,66,[149][150][151] Nanosizing of phytobioactive compounds along with suitable protective agents enhances the bioavailability of the compound to the brain. 24,72,95,145,152 A few of the bioactive nanosize compounds with enhanced bioactivity and less toxicity are discussed in this section. Some of these nanobioactive compounds are listed in Table 1.…”
mentioning
confidence: 99%
“…After stirring for another 30 min, the organic phase was separated, neutralized and washed with brine, dried by anhydrous sodium sulfate, filtered and condensed. The residue was recrystallized by ether to obtain PEG2000-carboxylmethyl active ester (10,16.71 g, 73.7%). Compound 10 (6 g, 2.6 mmol) was dissolved in 60 mL DMF and cooled to 0-5°C.…”
Section: Synthesis Of Peg-succinyl-lysine-res (Compound 2l)mentioning
confidence: 99%
“…[1][2][3] RES has received much attention in recent years because of its various health functions and its potential for use in medicinal applications. 4,5) Many studies have demonstrated that RES has significant pharmacological activity 6) and potential to be a chemopreventive and therapeutic agent for cancers, [7][8][9] Alzheimer's disease, 10) cardiovascular disease, 11) hyperlipidemia, 12) ischemia disease and other diseases. 13) Recently, RES has seen widespread use as a food ingredient and nutraceutical supplement in bread, cake and beverage products.…”
mentioning
confidence: 99%